2022
DOI: 10.3389/fevo.2022.768652
|View full text |Cite
|
Sign up to set email alerts
|

Gone With the Water: The Loss of Genetic Variability in Black and Gold Howler Monkeys (Alouatta caraya) Due to Dam Construction

Abstract: Black and gold howler monkeys (Alouatta caraya) inhabit several eco-regions in South America with the highest population densities in riverine forests. Dam construction for electricity production represents a severe human alteration of ecosystems with consequences for primate conservation. To evaluate the possible loss of genetic diversity in A. caraya, we analysed and compared the genetic structure of the species across 22 study sites in Argentina (14), Paraguay (1), and Brazil (7). Four of these study sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…This can be prevented by designating intraspecific conservation units such as Evolutionarily Significant Units (ESU) or Management Units (MU). An example of this regrettably late detection exists in the black-andgold howler monkey (Alouatta caraya) where a genetic study after the construction of dams showed that an entire genetic cluster of the species probably became extinct due to the flooding of populations with exclusive genetic characteristics (Oklander et al, 2022b). In this sense, the designation of MU in Alouatta guariba has been a very important precautionary measure.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…This can be prevented by designating intraspecific conservation units such as Evolutionarily Significant Units (ESU) or Management Units (MU). An example of this regrettably late detection exists in the black-andgold howler monkey (Alouatta caraya) where a genetic study after the construction of dams showed that an entire genetic cluster of the species probably became extinct due to the flooding of populations with exclusive genetic characteristics (Oklander et al, 2022b). In this sense, the designation of MU in Alouatta guariba has been a very important precautionary measure.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%